How Safe Is Life on the Road?: criminal Victimization Among a Sample of U.S. Nomads and the #VanLife Community - Whaley, Rachel Bridges (Crime & delinquency, 2023)
The current study provides the first estimates of criminal victimization prevalence among Nomads and members of the VanLife community. People who live and travel in manufactured recreational vehicles, retrofitted vans or buses, and cars are a heterogenous group who face an unknown risk of life on the road. Analyses reveal high victimization prevalence rates. Guided by lifestyle-routine activities theories, regression analyses reveal that gender, Latino ethnicity, income, and education affect risk of rape, aggravated assault, physical threats, property crime, aggravated property crime, and financial identity theft. Disaggregated analyses highlight those demographics that impact victimization risk for year-round Nomads versus part-timers. Questions about the lifestyles-routine activities of Nomads emerge from the analyses and directions for future research are offered.